DISPERSIÓN DEL INTERVALO QT CORREGIDO EN LA EVOLUCIÓN DE PACIENTES CON SÍNDROMES CORONARIOS AGUDOS / Corrected QT interval dispersion in the evolution of patients with acute coronary syndromes - Carlos J. Fabelo Mora; Juan M. Rodríguez Rueda; Frank Polanco Rodríguez; Luis O. Olivera Bacallao; Wilfredo de J. Machin Cabrera; Juan L. Pérez Chávez (CorSalud, 2011)
Introduction and Objectives: Acute myocardial infarc-tion remains a major challenge for health systems. In the classic concept of the ischemic cascade, the earliest event is the QT interval prolongation, which was previously reported in patients with unstable angina and ST elevation myocardial infarction. There has been speculation that the normalization of this interval in patients undergoing angioplasty, is a marker of successful reperfusion, thus the objective of this research is to characterize the corrected QT interval dispersion and its association with adverse outcomes in patients with acute coronary syndromes. Method: The corrected QT interval dispersion was analyzed in patients admitted to the Hospital "Comandante Manuel Fajardo Rivero" with an acute coronary syndrome from January to December 2009. The results were analyzed to provide inferential information on the basis of the statistical assessment of the SPSS processor, version 15.0. Results: The ST-segment elevation syndrome was the clinical form that included the most patients, but prolonged dispersion prevailed in those with unclassifiable syndrome, an atypical clinical presen-tation and a wrong electrocardiogram, similar behavior to that of the patients with a non-ST segment elevation syndrome, but not in those with ST segment elevation. Mortality, cardiac reinfarction, and need for myocardial revascularization were significantly associated with prolonged dispersion of the corrected QT interval. Conclusions: The prolonged dispersion of this interval could be an independent predictor of increased cardiovascular risk.